Economic costs of protecting islands from invasive alien species. Issue 2 (29th November 2022) - Bodey, Thomas W.; Angulo, Elena; Bang, Alok; Bellard, Céline; Fantle‐Lepczyk, Jean; Lenzner, Bernd; Turbelin, Anna; Watari, Yuya; Courchamp, Franck
Abstract: Biological invasions represent a key threat to insular systems and have pronounced impacts across environments and economies. The ecological impacts have received substantial focus, but the socioeconomic impacts are poorly synthesized across spatial and temporal scales. We used the InvaCost database, the most comprehensive assessment of published economic costs of invasive species, to assess economic impacts on islands worldwide. We analyzed socioeconomic costs across differing expenditure types and examined temporal trends across islands that differ in their political geography—island nation states, overseas territories, and islands of continental countries. Over US$36 billion in total costs (including damages and management) has occurred on islands from 1965 to 2020 due to invasive species' impacts. Nation states incurred the greatest total and management costs, and islands of continental countries incurred costs of similar magnitude, both far higher than those in overseas territories. Damage‐loss costs were significantly lower, but with qualitatively similar patterns across differing political geographies. The predominance of management spending differs from the pattern found for most countries examined and suggests important knowledge gaps in the extent of many damage‐related socioeconomic impacts. Nation states spent the greatest proportion of their gross domestic products countering these costs, at least 1 order of magnitude higher than other locations. Most costs were borne by authorities and stakeholders, demonstrating the key role of governmental and nongovernmental bodies in addressing island invasions. Temporal trends revealed cost increases across all island types, potentially reflecting efforts to tackle invasive species at larger, more socially complex scales. Nevertheless, the already high total economic costs of island invasions substantiate the role of biosecurity in reducing and preventing invasive species arrivals to reduce strains on limited financial resources and avoid threats to sustainable development goals. Abstract : Costos económicos de proteger a las islas de las especies invasoras Resumen: Las invasiones biológicas representan una amenaza importante para los sistemas insulares, además de tener impactos pronunciados en el ambiente y en la economía. Los impactos ecológicos han recibido atención sustancial, mientras que los impactos socioeconómicos se encuentran pobremente sintetizados en las escalas temporales y espaciales. Usamos la base de datos InvaCost, el análisis más completo de los costos económicos de las especies invasoras, para evaluar los impactos económicos sobre las islas a nivel mundial. Analizamos los costos socioeconómicos en varios tipos de gastos y examinamos las tendencias temporales en las islas que difieren en su geografía política – islas estado‐nación, territorios ultramarinos e islas de países continentales. En las islas han ocurrido gastos de más de $36 mil millones de dólares entre 1965 y 2020 debido a los impactos de las especies invasoras. Las islas estado‐nación produjeron los mayores costos de manejo y el mayor total, mientras que las islas de los países continentales produjeron costos de una magnitud similar, ambas con gastos mucho más elevados que los de los territorios ultramarinos. Los costos de las pérdidas por daños fueron significativamente más bajas, aunque con patrones cualitativamente similares entre las diferentes geografías políticas. El predominio del gasto en el manejo difiere del patrón hallado en la mayoría de los países analizados y sugiere que hay vacíos importantes en el conocimiento del alcance de muchos de los impactos socioeconómicos relacionados con los daños. Las islas estado‐nación gastaron la mayor proporción de su producto interno bruto en contrarrestar estos costos, al menos una orden de magnitud mayor que las otras localidades. La mayoría de los costos fueron asumidos por las autoridades y los accionistas, lo que demuestra el papel clave que tienen los organismos gubernamentales y no gubernamentales en cómo se atienden las invasiones insulares. Las tendencias temporales revelaron incrementos en el costo en todos los tipos de islas, lo que potencialmente refleja los esfuerzos por combatir a las especies invasoras a escalas más grandes y socialmente más complejas. Aun así, el elevado costo económico total de las invasiones insulares fundamenta la función que tiene la bioseguridad en la reducción y prevención de la llegada de especies invasoras para reducir presiones sobre los recursos financieros limitados y evitar amenazas para las metas de desarrollo sustentable. 【摘要】: 生物入侵是岛屿系统面临的主要威胁, 对环境和经济都产生了明显的影响。生态方面的影响已得到很多关注, 但社会经济方面的影响仍缺少时空尺度上的综合分析。本研究使用 InvaCost 数据库, 包含已发表的入侵物种经济成本最全面的评估数据, 来评估全球岛屿在生物入侵中面临的经济影响。我们分析了不同支出类型的社会经济成本, 并研究了不同政治地理的岛屿 (岛屿民族国家、海外领地和大陆国家的岛屿) 中社会经济成本随时间变化的趋势。结果显示, 从 1965 年到 2020 年, 岛屿由于入侵物种的影响产生的总成本 (包括破坏和管理) 超过 360 亿美元。民族国家的总成本和管理成本最高, 大陆国家的岛屿产生的成本规模相近, 都远远高于海外领地的成本。破坏导致的成本明显较低, 在不同政治地理的岛屿中有相似的情况。而管理支出占主导地位的情况则在我们研究的大多数国家中有所不同, 表明在许多与破坏有关的社会经济影响程度方面仍存在重要的知识空缺。民族国家用于这些成本的国内生产总值比例最高, 至少比其他地区高一个数量级。大多数费用由当局和利益相关者承担, 反映了政府和非政府机构在应对岛屿入侵问题中的关键作用。时间趋势分析表明, 所有类型的岛屿承担的成本都随时间推移而增加, 可能反映了在更大、更复杂的社会范围内应对生物入侵的努力。然而, 岛屿入侵问题的总经济成本已经很高, 这强调了应关注生物安全来减少和预防入侵物种的引入, 以减缓对有限财政资源的压力, 并避免对可持续发展目标的威胁。 【翻译: 胡怡思; 审校: 聂永刚】